1999
DOI: 10.1097/00000658-199908000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Wound Contraction in Stromelysin-1–Deficient Mice

Abstract: Excisional dermal wound healing is impaired in mice with a targeted deletion in the stromelysin-1 gene. Incisional wound healing is not affected. These data implicate stromelysin-1 proteolysis during early wound contraction and indicate that stromelysin-1 is crucial for the organization of a multicellular actin network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
1
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(158 citation statements)
references
References 31 publications
4
148
1
5
Order By: Relevance
“…This convincingly agrees with observations that keratinocytes from K5-Cre:STAT3flox/-transgenic mice show impaired mobility and migration in vivo and in vitro [39]. MMP3, a protease with a wide range of substrate specificities, degrades old multicellular actin networks thereby playing a role in wound contraction [40]. Temporal degradation of the extracellular matrix seems to also be important for antimicrobial defense, as MMP3-deficient mice show reduced migration of immune cells to the site of inflammation, which is associated with a delayed clearance of bacteria [41].…”
Section: Discussionsupporting
confidence: 90%
“…This convincingly agrees with observations that keratinocytes from K5-Cre:STAT3flox/-transgenic mice show impaired mobility and migration in vivo and in vitro [39]. MMP3, a protease with a wide range of substrate specificities, degrades old multicellular actin networks thereby playing a role in wound contraction [40]. Temporal degradation of the extracellular matrix seems to also be important for antimicrobial defense, as MMP3-deficient mice show reduced migration of immune cells to the site of inflammation, which is associated with a delayed clearance of bacteria [41].…”
Section: Discussionsupporting
confidence: 90%
“…Physiologically, MMP-3 expression was negligible in normal skin but was observed in keratinocytes after injury (7). Additionally, mice that lacked MMP-3 demonstrated impaired skin healing due to inadequate wound contraction but not keratinocyte migration (8). In support with this notion, our gene silencing experiment indicated that MMP-3 has limited effect on keratinocyte migration in our experimental condition.…”
Section: Discussionsupporting
confidence: 74%
“…In wounded Mmp7-mutant mice, epithelial cells do not migrate and E-cadherin cleavage does not occur 85 . MMP3 also functions in epidermal wound healing, as skin wounds of Mmp3-mutant mice heal more slowly than those of control mice, owing to a deficit in actin purse-string formation 86 .…”
Section: Mmp7 Is Involved In Innate Immunity and Wound Healingmentioning
confidence: 99%